Heat stress and uterine disease: Stressors influencing reproduction of dairy cattle - Voelz, Benjamin (Kansas State University, 2017)
Reproduction is an important part of a dairy operation that directly affects milk production and profitability. Fertility of high-producing dairy cows is less than desired. Reproductive efficiency is further impaired during summer months and after cows develop postpartum uterine disease. Heat stress and uterine disease act as stressors that negatively influence fertility of dairy cattle through a variety of mechanisms. This dissertation further investigates the negative effects of heat stress and uterine disease on reproduction, as well as examines two potential markers for predicting risk of developing uterine disease. Study 1 investigated the treatment of lactating dairy cows with gonadotropin-releasing hormone (GnRH) before first insemination during heat stress. Two experiments were performed to compare ovarian responses, pregnancy per artificial insemination (AI), and patterns of insemination of two estrus detection-based presynchronization protocols before first AI during summer heat stress. Treatment of cows with GnRH during summer heat stress altered ovarian response and pattern of insemination, however, did not improve pregnancy per AI. Study 2 evaluated ovarian response to treatment with GnRH and the odds of bearing a corpus luteum or being inseminated in cows with or without purulent vaginal discharge (PVD). Furthermore, hazard of insemination after administration of prostaglandin F2α was evaluated in dairy cows with or without PVD. Ovarian response was altered in cows with PVD compared with cows without PVD. Odds of bearing a corpus luteum or being inseminated was not associated with PVD in primiparous cows, whereas it was associated with PVD in multiparous cows. Hazard of insemination after prostaglandin F2α was not associated with PVD. Study 3 investigated arginase and matrix metalloproteinase-8 (MMP-8) as potential markers for metritis. Activity of arginase 7 days before parturition has been identified as a potential marker for the risk of developing metritis in dairy cows. In contrast, MMP-8 was not associated with the risk of developing metritis, therefore, MMP-8 is not a good candidate as a marker for metritis. Further research is warranted in the areas of reproductive physiology, heat stress, and uterine disease because several unanswered questions still exist. Improving fertility during times of heat stress and after the occurrence of postpartum uterine disease will improve milk production, animal welfare, and profitability of dairy farms across the world.
Keywords: Heat stress; Uterine disease; Dairy cow; Reproduction